Hydroxyl Group-Targeted Conjugate and Its Self-Assembled Nanoparticle of Peptide Drug: Effect of Degree of Saturation of Fatty Acids and Modification of Physicochemical Properties - Park, Jisoo; Ngo, Hai V.; Jin, Hyo Eon; Lee, Kye Wan; Lee, Beom Jin (International Journal of Nanomedicine, 2022)
Purpose: To conjugate different degree of saturation of C18 fatty acids (stearic acid, oleic acid, and linoleic acid) with the hydroxyl groups of leuprolide acetate (LEU acetate) and to investigate the controlled release and enhanced permeability through self-assembled nanoparticles (L18FNs). Methods: Yamaguchi esterification with benzoyl chloride and DMAP (4-Dimethylaminopyridine) allowed the conjugation of the fatty acid to the hydroxyl group of LEU. The three conjugates were then designated as stearic acid-conjugated LEU, LSC, oleic acid-conjugated LEU, LOC, and linoleic acid-conjugated LEU, LLC, respectively. The conjugates (L18FCs) were purified using pre-parative HPLC (Prep-HPLC) and identified through various instrumental analyses. Results: The zeta potential, particle size, and morphology of each L18FNs were evaluated. In the case of LSNs, the zeta potential value was relatively low and the particle size was larger than LONs and LLNs owing to the higher hydrophobicity of saturated fatty chain, while the LLNs showed a higher zeta potential and smaller particle size. In human plasma, LLC showed the fastest degradation rate with the highest accumulative drug release. The permeability of L18FNs was analyzed through the Franz diffusion cell experiment, confirming that the degree of saturation of fatty acids affects the permeability of LFNs. While the permeability of LSNs was not significantly enhanced due to higher particle size after nanonization, LONs and LLNs increased 1.56 and 1.85 times in permeation, respectively, compared to LEU. Conclusion: Utilization of different degree of saturation of fatty acids to conjugate a peptide drug could provide pharmaceutical versatility via self-assembly and modification of physicochemical properties.
Keywords: Fatty Acids; Humans; Linoleic Acid; Nanoparticles; Oleic Acid; Peptides; Stearic Acids; controlled release; different degree of saturation of C18 fatty acids; enhanced permeability; fatty acid-conjugated leuprolide; hydroxyl targeted conjugation; leuprolide acetate; self-assembled nanoparticles